PERCOBAAN PENDAHULUAN PETRO-PROTEIN (VITON) PADA ANJING DAN KERA 1) (SAFETY - TEST) 1972-1973 - Soekanto, Soekanto; Soedomo, Soedomo; Soejono, M.; Winoto, Winoto; Soetrisno, Joko; Soeriediarto, Haryo (Fakultas Peternakan UGM, 1974)
-